Fratura de fêmur: causas e perfil de idosos hospitalizados em Pelotas/RS, Brasil - Santos, Fernanda dos (2013)
Femur fracture is among the most common traumatic injuries in the elderly population, it presents a high mortality rate in the first year after fracture, it causes loss of functional capacity, resulting in about half of the elderly being unable to walk and in a quarter the need of extended care at home. The main objective of this research was to describe the causes of femur fractures and the profile of older adults with a diagnosis of femur fracture, hospitalized by SUS in the city of Pelotas / RS, Brazil. We opted for a cross-sectional descriptive study with elderly people who had femur fractures and were hospitalized in the Santa Casa de Pelotas Hospital, from February to August 2012. The variables were: Socioeconomic, demographic, and related to health / illness, besides the Mini Mental State Examination (MMSE). We interviewed 50 individuals, 39 women and 11 men. From the elderly fractured, mostly were white, retired, widowed, could read and write, and living with someone. Morbidity was prevalent hypertension with 56% of the sample, the majority reported continuous use of drugs and physical inactivity. The predominant mechanism of injury was falls occurred in the home of the elderly, and 78% of the elderly reported difficulty in walking before fracture. Regarding the tracking signs of dementia, 84% of elderly patients with femur fractures had cognitive impairment. Through the results presented in this research, and the aging of the population living in Brazil and in the city of study, it is relevant falls prevention campaigns among the elderly, with consequent promotion of improvement in the quality of life in this population.